Analisis Prediksi Risiko Kebangkrutan Berdasarkan Nilai Aset dan Liabilitas Menggunakan Metode Altman Z-Score: Studi Kasus Jiwasraya (Periode 2014, 2015, 2016, 2018, dan 2019) - Roufan Hirqoni Araniri; Angelita Buulolo; Tarikh Luthfi Simanjuntak; Jordan Ahmad Yasir; Dewi Hanggraeni (Universitas Muhammadiyah Ponorogo, 2021)
Jiwasraya is on the incisive edge. Based on 2019 Jiwasraya financial report, Jiwasraya’s ratio of solvency reached -18886.10% as of December 2019. By using the value of Jiwasraya's assets and liabilities based on the Jiwasraya Financial Statements for five periods (2014, 2015, 2016, 2018, 2019), the author used the Altman Z-Score analysis tool to measure the risk of Jiwasraya's bankruptcy. From the calculations using the Altman Z-Score, it can be concluded that Jiwasraya's Altman Z-Score is in the category of bankruptcy risk in 2014, 2018 and 2019 periods, while in 2015 and 2016, Jiwasraya's Altman Z-Score is in Grey area or it can be interpreted that Jiwasraya experienced financial distress in the 2015 and 2016 periods while there is still a possibility to avoid potential bankruptcy and the possibility of bankruptcy with the same magnitude.Keywords: Jiwasraya, Altman Z-score, kebangkrutan, Aset, Liabilitas.